2010
DOI: 10.1016/j.pain.2010.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphological changes associated with cyclic menstrual pain

Abstract: Primary dysmenorrhea (PDM) is the most prevalent gynecological disorder for women in the reproductive age. PDM patients suffer from lower abdominal pain that starts with the onset of the menstrual flow. Prolonged nociceptive input to the central nervous system can induce functional and structural alterations throughout the nervous system. In PDM, a chronic viscero-nociceptive drive of cyclic nature, indications of central sensitization and altered brain metabolism suggest a substantial central reorganization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 41 publications
7
168
1
2
Order By: Relevance
“…The left DLPFC was thinner and was activated abnormally in patients before treatment relative to controls; after treatment, the same region became thicker and also functioned more similarly to controls on a cognitive task. Previous research has shown altered brain anatomy in chronic pain conditions (Apkarian et al, 2004b;SchmidtWilcke et al, 2005SchmidtWilcke et al, , 2006Kuchinad et al, 2007;Buckalew et al, 2008;Geha et al, 2008;Lutz et al, 2008;Schweinhardt et al, 2008;Teutsch et al, 2008;Hsu et al, 2009;Obermann et al, 2009;Rodriguez-Raecke et al, 2009;Wood et al, 2009;Gwilym et al, 2010;Seminowicz et al, 2010;Tu et al, 2010), and other studies have linked cortical thickness to cognitive function (Hadjikhani et al, 2007;Dickerson et al, 2008;Sowell et al, 2008). To our knowledge, no other study has shown a link between gray matter density or cortical thickness loss and altered cognitive taskrelated brain activity in chronic pain.…”
Section: Discussionmentioning
confidence: 85%
“…The left DLPFC was thinner and was activated abnormally in patients before treatment relative to controls; after treatment, the same region became thicker and also functioned more similarly to controls on a cognitive task. Previous research has shown altered brain anatomy in chronic pain conditions (Apkarian et al, 2004b;SchmidtWilcke et al, 2005SchmidtWilcke et al, , 2006Kuchinad et al, 2007;Buckalew et al, 2008;Geha et al, 2008;Lutz et al, 2008;Schweinhardt et al, 2008;Teutsch et al, 2008;Hsu et al, 2009;Obermann et al, 2009;Rodriguez-Raecke et al, 2009;Wood et al, 2009;Gwilym et al, 2010;Seminowicz et al, 2010;Tu et al, 2010), and other studies have linked cortical thickness to cognitive function (Hadjikhani et al, 2007;Dickerson et al, 2008;Sowell et al, 2008). To our knowledge, no other study has shown a link between gray matter density or cortical thickness loss and altered cognitive taskrelated brain activity in chronic pain.…”
Section: Discussionmentioning
confidence: 85%
“…We speculate that the loss of complexity in PDMs could be attributed to the chronic stress elicited by recurrent menstrual pain. In our previous structural brain study, gray matter volume loss in regions of pain transmission, sensory processing, and affect regulation was found in PDMs [17]. Two resting-state fMRI studies reported trait-related hypoconnectivity between DMN and salience network during non-painful state [13,24].…”
Section: Measures Of Neural Complexitymentioning
confidence: 79%
“…Anterior cingulate cortex (ACC) engages in the emotional/motivational component of pain perception [125,126] and is a key region in the salience network (SAN) [102], which is activated when we constantly engage and focus on the pain but is normally deactivated when pain is gone. In a structural brain study [17], the gray matter volume of ACC was found the be increased in PDMs. We found that MSE in ACC is higher in PDMs compared to that in healthy controls, which suggest excessive attention processing of potential pain salience even in the absence of pain.…”
Section: Clinical Implications Of Altered Brain Complexity At Rest Inmentioning
confidence: 93%
See 1 more Smart Citation
“…Recurrent miscarriage and peri-implantation embryo failure have been attributed to inappropriate immune responses, with an excess of proinflammatory T H 1 cytokines relative to T H 2/3 type cytokines. Low-grade inflammatory changes (12), oxidative stress (13), hypomagnesemia (14), and characteristic morphologic changes in the hypothalamus (15) have been associated with premenstrual mood changes, dysmenorrhea, and failure of assisted reproductive technologies.…”
mentioning
confidence: 99%